The Influence of the Role of Leadership and Compensation on Employee Performance of PT Taiho Nusantara - Dedi Mulyadi (International Journal of Science and Society, 2020)
This research was conducted to find out how much influence the leadership and compensation have on the performance of the employees of PT Taiho Nusantara partially and simultaneously. The method used in this research is descriptive and verification. The population is all employees of PT Tiho Nusantara by taking 105 employee samples. The data collection techniques are through interviews, questionnaires and observations, and data analysis used Path Analysis. The results showed that the correlation between variables X1 and X2 obtained the magnitude of the correlation coefficient between the independent variables, namely the role of leadership (X1) with compensation (X2) can be valued at 0.875. Thus the role of leadership (X1) with compensation (X2) has a strong and two-way relationship because of its positive value. And for the influence of the leadership role variable (X1) on employee performance variables (Y) is 0.382. This shows that the direct influence of the leadership role variable (X1) on employee performance variables (Y) is 0.392 so that the equation Y = 0.382 X1 is obtained. And the results for the Compensation variable (X2) against employee performance variables (Y) are 0.587. This shows that the direct effect of the Compensation variable (X2) on employee performance (Y) is equal to 0.575 so that the equation Y = 0.587 X2 is obtained. Then the path of the storage role variable (0.382) is lower than the compensation variable (0.587), meaning that compensation (X2) has more influence on employee performance (Y). While the influence of leadership roles (X1) and compensation (X2) simultaneously (overall) on employee performance (Y) with the result that the value of sig. (0,000) <α (0.05) and tcount (379,050)> ftable (3.09) then Ho is rejected. Thus it can be concluded that the role of leadership and compensation simultaneously influences the performance of its employees.